Efficiency of Oviparasitoids (Sugonjaev and Sorokina) Trichogrammma Principium, Romini Growth Regulator and Pesticide before Integration in Control of Roundworm Spodoptera litoralis (Boisduval) (Lep: Noctuidae) (Journal of the College of Basic Education, 2022)
Laboratory and field studies were carried out to test the efficacy of Trichogramma principium, growth regulator Dimilin and Avant in controlling cotton leafworm. The field results, one week after the release of the Trichogramma principium, indicated that the parasitoids reduced the density of eggs by one mass, while the average eggs in the control treatment were 1.66 masses. A laboratory experiment was conducted that included evaluating the efficiency of the growth regulator Dimilin on the life of the third and fourth larval ages of the cotton leafworm. Spodoptera litoralis, the first two treatments were conducted for direct spraying, as it gave a death rate of about 73 and 66% for the third and fourth instars after 3 days of treatment, respectively, and the second feeding treatment gave death rates for larvae about 56.7 and 47.7% for the third and fourth instars, respectively.